The Use of Digital Media in Learning Islamic Religious Education: Opportunities and Challenges - Emi Rohmiati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to examine the use of digital media in learning Islamic Religious Education (PAI). Through literature analysis, this study found that digital media has great potential to improve the quality of Islamic Education learning. The use of technologies such as e-books, learning videos, interactive applications, augmented reality (AR), and virtual reality (VR) can improve students' accessibility, interactivity, learning motivation, and digital competence. However, the research also identified several challenges, including technology infrastructure readiness, teacher competency, and safety and ethical aspects of technology use. To overcome these challenges, proposed solutions include strengthening technology infrastructure, improving teachers' digital competencies through continuous training, developing digital ethics policies and guidelines, and close supervision during learning. The findings of this study make an important contribution to the development of the theory and practice of Islamic religious education in the digital era and can serve as a reference for educators, policymakers, and researchers. Further research is needed to explore unreached aspects and assess the effectiveness of the proposed strategies